DOXAZOSIN AND MELOXICAM COMBINATION THERAPY FOR BPH TREATMENT WITH LUTS - Suarsana, Wayan; Hardjowijoto, Sunaryo; Wirjopranoto, Soetojo; Budiono, Budiono (Indonesian Urological Association, 2014)
Objective: To compare the efficacy of combination therapy of 4 mg doxazosin + 15 mg meloxicam with 4 mg doxazosin single therapy for benign prostate hyperplasia (BPH) patients with lower urinary tract symptoms (LUTS). Materials & Methods: A prospective, randomized and double blind study with total of 22 BPH patients with LUTS were randomized to receive 4 mg doxazosin + placebo once daily for 6 weeks or a combination of 4 mg doxazosin + 15 mg meloxicam once daily for 6 weeks. Inclusion criteria included IPSS ≥ 8, age > 50 years, prostate blood flow grade II. Therapeutic efficacy was assessed by comparing changes in IPSS, maximal urinary flow (Q-max) and changes in prostate blood flow between baseline and immediately after 6 weeks of therapy. Results: There was no significant difference in IPSS change between the two treatment groups (delta IPSS 4 ± 1.1 versus 3.7 ± 1.5, p = 0.630). There was a significant difference in Q-max changes between the two groups (delta Q-max 4 ± 1.5 versus 2.1 ± 0.7, p < 0.001). In group therapied with 4 mg doxazosin + 15 mg meloxicam prostate blood flow decreased from grade II to grade I in 9 of 11 patients (81%). Whereas, in the treatment group of 4 mg doxazosin + placebo no reduction was found in prostate blood flow. Conclusion: Combination therapy of 4 mg doxazosin + 15 mg meloxicam once daily for 6 weeks is better than 4 mg doxazosin therapy alone in improving Q-max and decreasing prostate blood flow in BPH patients with LUTS.Keywords: Benign prostate hyperplasia, inflammation, COX-2 inhibitors.